Learning from the experience of anniversary self-service. - Mikhailova, N.P. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2026)
In this article, the author shares memories of her life and scientific journey on the eve of her 100th anniversary, which falls in 2026. She recounts the history of her family, her childhood during World War II, her choice of profession, and her subsequent studies. Considerable attention is given to her many years of work at the Institute of Geophysics, the development of paleomagnetic research in Ukraine, international cooperation, and the colleagues who accompanied her along the way.